BEYOND CONVENTIONAL JOURNALING: LEVERAGING SOCIAL MEDIA MICRO-BLOGGING PLATFORMS TO FOSTER INTERACTIVE AND ENJOYABLE LEARNING REFLECTIONS IN THE DIGITAL ERA - Rifka Rindika Alwi; Dwi Rizka Amalia; Marianus Serpulus Firmanto; Achmad Fajar Muhammad; Restu Januarty Hamid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of information and communication technology has brought significant changes to the field of education, particularly in students' learning patterns in the digital era. Instagram and TikTok, which were initially known as entertainment platforms, are now increasingly being utilized as learning support media. This study aims to examine how students use Instagram and TikTok as learning strategies and as media for learning reflection in higher education. This study employed a descriptive qualitative approach using a purposive sampling technique. The research subjects consisted of 50 active students from several universities in South Sulawesi, particularly in the cities of Makassar, Bone, and Barru, who belong to the digital native generation. Data were collected through open-ended questionnaires and short interviews. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that students utilize Instagram and TikTok not only as entertainment platforms but also as alternative learning media. TikTok is used to access tutorial videos, concise explanations of learning materials, and practical study tips that are easy to understand. Meanwhile, Instagram is utilized through micro-blogging features such as Instagram Stories to share learning progress, learning reflections, and academic interactions. The use of these platforms has positive impacts, including increased learning motivation, easier access to information, enhanced student creativity, and more interactive learning experiences. This study demonstrates that social media has substantial potential as a supporting learning medium in the digital era, particularly for digital native generations within higher education environments.